2020
DOI: 10.1007/s00268-020-05802-w
|View full text |Cite
|
Sign up to set email alerts
|

In‐Hospital Postoperative Mortality Rates for Selected Procedures in Tanzania's Lake Zone

Abstract: Background Postoperative mortality rate is one of six surgical indicators identified by the Lancet Commission on Global Surgery for monitoring access to high-quality surgical care. The primary aim of this study was to measure the postoperative mortality rate in Tanzania’s Lake Zone to provide a baseline for surgical strengthening efforts. The secondary aim was to measure the effect of Safe Surgery 2020, a multi-component intervention to improve surgical quality, on postoperative mortality after 10 months. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
2
7
2
Order By: Relevance
“…This study found that the 28 days postoperative mortality at Tibebe Ghion Specialised Hospital was 3.69%, with an incidence rate of 1.37 deaths per 1000 person-day observations. This result is comparable with studies done in Ethiopia24–27 and South Africa,17 but it was higher than most studies conducted in LMIC 7 22 28–31. Our finding was also higher than the African Surgical Outcomes Study report conducted in 25 African countries 8.…”
Section: Discussionsupporting
confidence: 84%
“…This study found that the 28 days postoperative mortality at Tibebe Ghion Specialised Hospital was 3.69%, with an incidence rate of 1.37 deaths per 1000 person-day observations. This result is comparable with studies done in Ethiopia24–27 and South Africa,17 but it was higher than most studies conducted in LMIC 7 22 28–31. Our finding was also higher than the African Surgical Outcomes Study report conducted in 25 African countries 8.…”
Section: Discussionsupporting
confidence: 84%
“…In‐hospital mortality was 0.9% in this dataset, equivalent to 9/1000. This was lower than reported rates of around 2% in Uganda [22], Tanzania [23] and the multi‐country African Surgical Outcomes Study [21], albeit with a smaller cohort of patients. Infection is the most common postoperative complication reported across Africa, with rates of 6.8–26% reported [24].…”
Section: Discussioncontrasting
confidence: 70%
“…In-hospital mortality was 0.9% in this dataset, equivalent to 9/1000. This was lower than reported rates of around 2% in Uganda [22], Tanzania [23] and the multi-country African Surgical…”
Section: Median (Iqrcontrasting
confidence: 71%
“…In 2018, a multimodal mentorship component of a Safe Surgery 2020 (SS2020) intervention was implemented to build surgical care provider capacity in 10 health facilities in Tanzania’s Lake Zone. SS2020 had two goals: (1) improve surgical quality processes including safety practices, teamwork and communication, and data quality, and (2) reduce postsurgical infections [ 8 , 9 , 27 , 33 35 ]. Mentorship was the final phase of SS2020 and was designed to support technical and non-technical skill development for non-specialist providers to improve surgical quality, following training [ 8 ].…”
Section: Introductionmentioning
confidence: 99%